TA’LIM SOHASIDA RAQAMLI TEXNOLOGIYALARNI JORIY QILISH – IJTIMOIY PEDAGOGIK ZARURIYAT SIFATIDA - Xamzayev, Х.Х. (SCIENCE and SOCIETY, 2024)
The article analyzes the importance and role of using online courses, elements of digitization of education, and digital technologies in the higher education system.
Keywords: higher education; classical education; digitization of education; electronic education; legislation